Association between disorganization of the retinal inner layers and capillary nonperfusion area in patients with retinal vein occlusion - Goker,Yasin Sakir (2020)
ABSTRACT Purpose: To determine the correlation between the extent of disorganization of the retinal inner layers (a parameter of spectral domain optical coherence tomography) and optical coherence tomography angiography parameters in eyes with center-involved macular edema associated with retinal vein occlusion. Methods: This retrospective observational study included 34 eyes of 34 patients with newly diagnosed macular edema associated with retinal vein occlusion and evidence of center-involved macular edema. Optical coherence tomography angiography and spectral domain optical coherence tomography were evaluated after resolution of the macular edema. Disorganization of the retinal inner layers was determined via spectral domain optical coherence tomography and optical coherence tomography angiography parameters, including foveal avascular zone area in the superficial capillary plexus and capillary nonperfusion areas, foveal avascular zone area in full retinal vasculature, foveal avascular zone perimeter, acircularity index of the foveal avascular zone, and foveal density. Results: The mean disorganization of the retinal inner layers extent was 512.72 ± 238.47 microns, and the mean capillary nonperfusion area was 4.98 ± 2.85 mm2. There was a positive correlation between the extent of disorganization of the retinal inner layers and capillary nonperfusion area (p<0.001, r=0.901). Greater extent of disorganization of the retinal inner layers and the capillary nonperfusion area was correlated with wider foveal avascular zone area (p=0.014 and p=0.036, respectively) in the superficial capillary plexus and decreased foveal density (vessel density in 300 microns around the foveal avascular zone) (p=0.031 and p=0.022, respectively). These parameters were also correlated with decreased vessel density in both the superficial capillary plexus and deep capillary plexus in the parafoveal and perifoveal regions (p<0.05 for all). Conclusions: Disorganization of the retinal inner layers appears to be a correlated biomarker of capillary ischemia in retinal vein occlusion. The extent of disorganization of the retinal inner layers was strongly correlated with the capillary nonperfusion area. This may support the notion that the extent of disorganization of the retinal inner layers can be used as an easily obtainable and crucial surrogate marker of capillary ischemia.